Self-care and spirituality in volunteer psychologists during the Covid-19 pandemic (Research, Society and Development, 2022)
This work is an integral part of a master's thesis whose objective was to unveil the perceptual experience and the meaning of life for volunteer psychologists who have served online amid the Covid-19 pandemic. In this qualitative study, the self-care of these professionals is approached in different ways, as it is a multidimensional and multifaceted concept involving areas and dimensions of personal and professional life. In the scenario of the current pandemic, with all its particularities, the self-care of psychologists contributes to the relief of stress, helping in their personal and professional life. This study was conducted to identify how volunteer psychologists had experienced their self-care in the face of the demands brought by their clients. The objective was to understand whether spirituality acts as a protective factor. A sample of 20 professionals, of which 90% were females, participated in the study. Self-care strategies were identified that proved effective in dealing with the exhaustion caused by clinical practice. The importance of using resources from the spiritual dimension was verified as a source of strength to live. Belief in God, and the help of prayer, offer confidence and support to overcome life's obstacles, especially in a period of social isolation.